Implementasi Program Gerakan Literasi Sekolah (GLS) di Kota Padang Panjang - Aisyah Tul Ummah; Azwar; Maihasni (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
The School Literacy Movement (GLS) program is a government initiative aimed at developing character and shaping students' characters through cultivating a literate ecosystem. This program is implemented in a participatory manner at all levels of primary and secondary education, and is based on Permendikbud Number 23 of 2015 to increase interest and awareness of literacy among students. This study aims to describe the implementation of GLS in Padang Panjang City with a focus on four schools: SDN 03 Padang Panjang Timur, SMPN 1 Padang Panjang, SMAN 1 Sumatera Barat, and SMKN 1 Padang Panjang. This study uses a descriptive qualitative approach with informants selected purposively. Data were collected through in-depth interviews, observations, and document studies. The analysis uses Pierre Bourdieu's theory of habitus, capital, and arena. Habitus refers to the literacy habits of teachers and students that influence program acceptance, while various forms of capital economic (BOS and DAK funds), symbolic (achievements, facilities), social (external cooperation), and cultural are supporting factors for GLS implementation. The results of the study showed differences in approaches between levels of education. At the elementary school level, literacy is implemented through the learning while playing method. Meanwhile, junior high schools and senior high schools/vocational schools are more varied in activities, such as strengthening the role of libraries, reading corners, wall magazines, literacy competitions, the formation of literacy teams, and the use of digital technology. The success of the program is highly dependent on the commitment and collaboration of all elements of the school. Keywords: Program Implementation, Literacy, School Literacy Movement (GLS)